Y-Stent Rescue Technique for Failed Thrombectomy in Patients With Large Vessel Occlusion: A Case Series and Pooled Analysis - Li, Zifu; Liu, Peng; Zhang, Lei; Zhang, Yongwei; Fang, Yibin; Xing, Pengfei; Huang, Qinghai; Yang, Pengfei; Liu, Jianmin (Frontiers in Neurology, 2020)
Objective: Y-stent thrombectomy is a recent rescue technique for failed thrombectomy in patients with emergent large vessel occlusion. We presented case series of using Y-stent rescue technique at different sites and investigate its feasibility and safety through pooled analysis of collected case report or series. Methods: Twenty-eight cases were screened from stroke databank who underwent thrombectomy between January 2015 and June 2019. Clinical, procedural, and follow-up data were investigated and pooled analysis of published literature was analyzed. Results: The occlusion sites include carotid terminus in 14 patients; siphon segment in 3; middle cerebral artery (MCA) in 4; basilar terminus in 7. The overall recanalization rate reached 85.7% (arterial occlusive lesion score 2–3); and final reperfusion rate 85.7% (modified Thrombolysis in Cerebral Infarction 2b−3). After literature review, totally, 52 cases were included. Good clinical outcome was achieved in 26 (50%) and mortality in 7 (17.3%). There is no significant difference on the SAH complication at different sites. Literature review shows no difference between each site in the reperfusion and complication rate. Conclusion: Our case series results suggest that high recanalization rate can be effectively achieved with Y-stent rescue technique for patients with refractory emergent large vessel occlusion. The safety of using this technique at different sites needs further investigation for patients.